Perceptions of nursing staff regarding the existence of best practice standards in selected private hospitals in eThekwini district, South Africa - Jamila Chellan; Maureen Nokuthula Sibiya (Elsevier, 2018)
In South Africa, the National Core Standards (NCS) are advocated as the cornerstone for improving quality and patient safety in health care organisations. To align to the Department of Health's legislative and policy mandates, the Office of Health Standards Compliance developed the NCS for Health Establishments in South Africa that provide a benchmark of quality of care against which the delivery of health services can be monitored. Through the implementation of the NCS, an assessment of a health facility's compliance to service standards can be measured. The aim of the study was to assess the perceptions of nursing staff regarding the existence of best practice standards in relation to the NCS and Batho Pele Principles. Batho Pele can be viewed as an approach which places the people first. It can be also stated that Batho Pele is a framework which guides healthcare organisations to be more focused on patient needs (Republic of South Africa, 1997). An exploratory descriptive study using a quantitative design was used to conduct the study at a group of four private hospitals in eThekwini district coded as Hospital A, B, C and D. The total population of nurses was 569 of which 270 were sampled for the study. A total of 270 questionnaires were distributed. The total number of questionnaires that were received and included in the data analysis and interpretation was a total of 234 from all four hospitals. The results of the study showed that the overall return rate in the quantitative phase of the study was measured at 86.66%. There was significant agreement by the nursing staff across the four hospitals in the group that best practice standards for patient care existed in selected private hospitals in eThekwini district, related to the Patient Rights, Patient Care and Support Services domains. A follow up phase of documentation review of policies, procedures and directives as identified by the participants was undertaken to validate the findings of the results. The goal now is for ongoing education and training to ensure best practice standards are consistently applied for safe patient care. This requires management commitment and responsibility in the form of education and training, at operational and unit level. It is important that these levels of hierarchy co-operate to implement and sustain best practice standards and processes within the group of hospitals to conform to the National Quality Framework of the NCS and Batho Pele principles. Keywords: Quality, Best practices, Patient care, Patient rights, Support services